6x+2(2x-9)=32

Simple and best practice solution for 6x+2(2x-9)=32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+2(2x-9)=32 equation:


Simplifying
6x + 2(2x + -9) = 32

Reorder the terms:
6x + 2(-9 + 2x) = 32
6x + (-9 * 2 + 2x * 2) = 32
6x + (-18 + 4x) = 32

Reorder the terms:
-18 + 6x + 4x = 32

Combine like terms: 6x + 4x = 10x
-18 + 10x = 32

Solving
-18 + 10x = 32

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 10x = 32 + 18

Combine like terms: -18 + 18 = 0
0 + 10x = 32 + 18
10x = 32 + 18

Combine like terms: 32 + 18 = 50
10x = 50

Divide each side by '10'.
x = 5

Simplifying
x = 5

See similar equations:

| 100=70x+3000 | | 24x^7y^1-96x^3y^3= | | 6-10+2/2= | | 3(x-2)=x-18 | | d+4d+5d=180 | | ln(x-4)-ln(x-5)=4 | | 10y+44+48-2y=156 | | -9y+3y-7=6+4y-13 | | V/23=11 | | 5n-8=2 | | 3(40)-15=x+25 | | 4+m=3m | | n/10+6=12 | | 3x-2=24x-23 | | n/10+6=14 | | X^2-19x+14=-70 | | 3(x+5)=2x+1 | | x=-5(1) | | 8-4x=28-2x | | 12cos(3x)=0 | | 7x+13-9x=20-18x+16x-7 | | -14-5x=13-6x | | 9x^2-21x+7=-3 | | 7+13n= | | 8-4x=28-4x | | y-6x=13x | | x^2=364 | | X^2-17x+44=-4x+2 | | 8x+10y=106 | | 1.2=x-2.76 | | 2x+15=3x+10 | | 7+8n= |

Equations solver categories